Pengaruh Kualitas Penyelenggaraan Special Event dan City Branding Terhadap Destinasi Pariwisata di Kawasan Geopark Ciletuh Kabupaten Sukabumi - Prakoso, Ganang Aditiyo (Jurnal Ilmiah Pariwisata, 2021)
This study aims to determine the quality of organizing special events and city branding of tourist destinations in the Ciletuh Geopark area, Sukabumi Regency. This research uses multiple regression analysis method. Respondents in this study were the government, tourism managers, tourists and the community by providing a questionnaire with a Likert scale. The total population is 1,371,367 inhabitants. While the sample amounted to 139 people using the Slovin formula. The results of this study partially show that the quality of organizing special events has no significant effect on tourism destinations. While partially the quality of city branding has a significant effect on tourism destinations. Ciletuh Geopark is an area that is part of the UNESCO Global Geopark as an attraction that attracts tourists to visit, with many natural and cultural attractions that are still very strong in the local community. For the Indonesian Fishermen's Association, establishing broader relationships with stakeholders is useful in improving the quality of the organization, both in terms of marketing and the implementation of the Palabuanratu Fisherman Day Festival. The government is expected to be able to catalog events, so that visitors have the desire to explore tourist destinations. Keywords: Quality of Organizing Special Events, City Branding, Tourism Destinations